Representasi Makna Denotasi Pada Pesan Moral Season 1 Anime Sousou No Frieren - Fairuz Anwidati Zahiyyah (CV. ITTC INDONESIA, 2024)
Motivation is something that can raise someone's spirit when they are tired of facing everyday life. Not a few people have difficulty getting motivation for themselves or others. This study aims to determine the motivation of moral messages in Season 1 of the Sousou No Frieren Anime. The method used in this study is descriptive qualitative with Roland Barthes' Semiotic analysis. The results of this study indicate the denotative meaning of the Sousou No Frieren anime contained in 23 scenes in 8 episodes that describe motivation that can raise enthusiasm or make oneself aware of things that should or should not be done.